Participation of various habitat groups in the flora of spring niches in the Ojców National Park (Southern Poland) - Sołtys-Lelek, Anna; Barabasz-Krasny, Beata; Różkowski, Jacek (Biodiversity: Research and Conservation, 2015)
The paper presents composition of vascular plant species in spring niches in the Ojców National Park (Southern Poland). 111 species of vascular plants, fourteen mosses, two liverworts and one species of ferns were recorded during the first comprehensive study carried out in 2009 and 2010. Plants occurring in these places showed different degrees of association with spring niches. The largest group was represented by accidental krenophytes (74 species), while spring plants - obligatory krenophytes, constituted only a small part of the local flora (5 species). Meadow species of the Molinio-Arrhenatheretea class and forest species of the Querco-Fagetea class, penetrating niche areas from the adjacent areas, were the dominating ones. Plants of aquatic and spring communities were scarce, due to the predominance of small type karst springs. The diversity of vegetation was significantly influenced by habitat factors such as availability of light, humidity or the amount of organic matter in the soil.